2015
DOI: 10.1111/ecc.12331
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Kinesiology Taping on the volume of lymphoedema and manual dexterity of the upper limb in women after breast cancer treatment

Abstract: The aim of our study was to evaluate the effect of Kinesiology Taping (KT) on the size of lymphoedema and manual dexterity of the upper limb in women after breast cancer treatment. We also examined whether the application of KT can replace the traditional and standard multilayered bandaging in the treatment of upper extremity lymphoedema. Group A comprised of 22 patients who underwent KT as well as pneumatic and manual lymphatic drainage. Then, group B comprised of 23 patients who were treated with quasi-KT as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
12

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 14 publications
1
42
0
12
Order By: Relevance
“…Furthermore, Taradaj et al . () found a statistically significant difference between the interventions.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…Furthermore, Taradaj et al . () found a statistically significant difference between the interventions.…”
Section: Resultsmentioning
confidence: 85%
“…Taradaj et al . () found a statistically significant decrease in limb volume in all groups (KT 778.7 ± 739.8 mL, bandaging 1200 ± 580.8 mL) but also reported that the greatest oedema reduction was in the bandaging group. Furthermore, Taradaj et al .…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…35 37-40 Two studies on the other hand found that kinesiology taping was not superior to the multilayered bandaging when combined with manual lymphatic drainage and pneumatic compression for reducing breast cancerrelated stage 2 or 3 lymphoedema. 41 42 Nevertheless, kinesiology taping was associated with improvements in limb volume reduction and upper limb ROM, 42 which could be of clinical relevance in patients that are ill-suited to the multilayered bandaging. Overall, it seems kinesiology taping may not be superior to existing therapies for lymphoedema management but may be useful in select patients with early stage I and II lymphoedema.…”
Section: Introductionmentioning
confidence: 99%